Does ICT Favor Vulnerable Group? Evidence from Poverty and Inequality Alleviation in Eastern Indonesia - Khusniati, Navi'ah (SAFE-Network, 2025)
The advancement of information technology has resulted in various economic effects. This study examines how access to Information and Communication Technology (ICT) influences poverty and income inequality in Eastern Indonesia, using panel data from 12 provinces between 2014 and 2024. To address potential endogeneity issues like reverse causality and omitted variable bias, the research utilizes Instrumental Variables (2SLS) models for estimation. The findings indicate that while there is a negative correlation between increased internet access and poverty levels, this relationship loses its causal significance once endogeneity is considered. Conversely, ICT consistently shows a negative and significant impact on income inequality, particularly evident in the model. This suggests that ICT is more effective in addressing inequality than in directly reducing poverty. Furthermore, structural factors such as unemployment, electrification, and GRDP per capita play a significant role in shaping the economic welfare dynamics in Eastern Indonesia. The study highlights that digital development can only be inclusive when supported by equitable infrastructure and high-quality human resources.